Model of sickle kick pencak silat training based on exercise media in students pencak silat athletes - Amrullah, Ramdani; Dlis, Firmansyah; Hernawan, Hernawan (Journal of Education, Health and Sport, 2020)
Introduction. Techniques kick is most often used in competition and in the game self-defense more than 90% points scored by the kick competition that kicks effectivenessdepending on various factors, such as the maximum strength of the muscles involved in the level of development of strength, coordination neoromuscular, the linear velocity and the angle of the ankle when kicking leg and improve coordination between agonists and antagonists. develop a model exercise kick sickle-based media practice, because the model through the medium of exercise is a model of long-term and continuous change constantly, because this type of training will develop with regard to the development of athletes in accordance with the specifications of the branch sport, and System and method of exercise is getting day also thanks to the support of increasingly sophisticated equipment, facilities and infrastructure that is more modern. Objective of the study. This study aims to determine whether the basic Technicalskills learning model based media workout sickle kick effectively improve the skills and abilities of the sickle kick pencak silat sport student athletes. Research methods. Studies that use mixed methods research approach that combines qualitative and quantitative methods.Research Quantitative used to find the effectiveness of the True-Experimental research design shaped the pretest-posttest control group design. Research result. Initial tests ability sicklekick right and left of 6.944, 6.39. 65.22 skill being right, and left 71.26. after being given treatment ability right sicklekick 8.70 and 8.04 left. Skills right 62.48, 68.66 to the left. Conclusion.Based on the results of data from field trials and discussions can be concluded that this type of training with exercise effective media to enhance the capabilities and skills of the sickle kick sports pencak silat students.